HEALTH BELIEF MODEL DALAM PENGOBATAN TRADISIONAL SITUNGKIR - Popy Ivanda Putri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The purpose of this research was to find out what factors a person chooses traditional medicine, especially in Situngkir medicine as a place for traditional treatment. In this study using a method that is descriptive qualitative. At the time of the research, the determination of subjects was carried out using the Acidental Sampling technique, namely the determination of random samples that happened to be found at the research location. The results of this study are informants as patients undergoing treatment at Situngkir which is based on 6 factors, namely Perceived Severity, namely the severity of a disease, Perceived Susceptibility, namely perceived vulnerability, Perceived Benefits, namely perceived benefits, Perceived Barriers, namely perceived barriers, Cues to Action, namely decision making on the basis of a recommendation, and Self-efficacy, namely individual confidence in taking an action. In this research about a person's beliefs in making a decision in choosing a place of treatment, and finally choosing in Situngkir. Keywords: Belief, Tradisional Treatment, Health Belief Model